The Effect of Young Papaya Seed Extract on the Number of Male Mice Spermatozoes (Mus musculus) - Tannya Efritzka Louise Calame; Kusmiyati Kusmiyati; I Wayan Merta (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
Papaya fruit has many benefits, one of which is papaya seed can be used as antifertility drugs especially young papaya seeds. This is because young papaya seeds contain secondary metabolites of alkaloid glycosides and proteolytic enzymes such as papain which can interfere with spermatogenesis. This aims to determine the effect of young papaya seed extract of a mice number spermatozoa. Mice were randomly selected to represent 4 dose groups: control group (P0), extract 30mg/BW (PI), extract 60mg/BW (PII) and extract 90mg/BW (PIII). Each treatment group was carried out with six repetitions. The treatment was given intravenously by injecting it in the tail of the mice for 15 consecutive days. The observed spermatozoa quality variables is a number of spermatozoa. Data analysis used one way ANOVA significance test 5% (p<0,05) and continuedÃÂ with the LSD (Least Significant Difference) 95% confidence. The result of the study on the quality of spermatozoa showed a significant effect at the doses of 60mg/BW (PII) and 90mg/BW (PIII). The higher dose of young papaya seed extract, it increasingly affects the number of sperm. The research concluded that the extract of young papaya seeds has a significant impact of a mice number spermatozoa (Mus musculus).